Reliance on External Assurance in Regulatory Monitoring - Gopalan, Yadav K.; Imdieke, Andrew J.; Schroeder, Joseph H.; Stuber, Sarah B. (The Accounting Review, 2024)
ABSTRACT We exploit a regulatory change to examine whether bank regulator strictness is affected when regulators no longer rely on external assurance. In the absence of external assurance, we find that banks report higher nonaccrual loans, higher troubled debt restructurings, and both a timelier loan loss provision and higher quality allowance for loan loss reserve. Further, regulators spend more days performing targeted bank examinations for banks affected by the regulatory change. We do not find evidence of operational deterioration, but rather the findings are consistent with increased regulator strictness over the reporting of problem assets, particularly during targeted examinations. Overall, our results suggest that regulators become stricter when they can no longer rely on the work of external auditors and that third-party assurance is an imperfect substitute for direct regulatory monitoring. Data Availability: Bank regulatory rating and examination dates are confidential and were obtained from the Federal Reserve Bank of St. Louis. All other data are available from the public sources cited in the text. JEL Classifications: G21; G28; M42.